The Effect of Project-Based Learning Model in Junior High School Students’ Creative Thinking Skills - Melda Oktavia; Skunda Diliarosta (SEMESTA: Journal of Science Education and Teaching, 2026)
Creative thinking skills are essential to develop through the learning process to enable students to solve various learning-related problems and to meet the demands of the twenty-first century. Therefore, innovation in learning models is required to enhance students’ creative thinking abilities. One such model is Project-Based Learning (PjBL). This study aimed to examine the effect of the PjBL model on junior high school students’ creative thinking skills in the context of Indonesian ecology and biodiversity. A quasi-experimental method with a nonequivalent control group design was employed. The research subjects were two classes of SMP Negeri 35 Padang, consisting of an experimental class taught using the PjBL model and a control class taught using conventional instructional methods. Data were collected through pretests and posttests and analyzed using a t-test. The results indicated that students’ creative thinking skills in both classes were equivalent prior to treatment. After the intervention, the experimental class showed a significant improvement in creative thinking skills (tcount = 3.267 > ttable = 1.670). These findings demonstrate that the PjBL model has a significant positive effect on students’ creative thinking abilities.